ORGANIZATION OF THE COMPREHENSIVE REHABILITATION SYSTEM BASED ON STUDYING NEEDS OF PERSONS WITH DISABILITIES IN THE RUSSIAN FEDERATION - Оксана Николаевна Владимирова; Кира Павловна Афонина; Геннадий Николаевич Пономаренко; Александр Владимирович Шошмин (Медицина в Кузбассе, 2018)
Objective. The study was focused on the needs of persons with disabilities in medical rehabilitation to be considered while organizingsystems of rehabilitation in Russian regions. The aim of the study was to analyze the needs of persons with disabilities in the Russian Federation in the light of the human rights model of disability.